IMPLEMENTATION OF QUESTION CARD ASSISTED TAPPS ON STUDENT LEARNING OUTCOMES AND ACTIVITY - Ulfa Lutfianasari; Mohammad Agus Prayitno; Nur Alawiyah (Jurnal Education and Development, 2021)
This study aims to determine the effectiveness of the application of the TAPPS model assisted by Question Cards on student learning outcomes and activeness. The population in this study were students of class XI-IPA at SMA Negeri 1 Karanganyar, Demak. Determination of the sample using the purposive sampling system obtained two classes to be sampled, namely class XI-IPA2 as the experimental class which was treated using the TAPPS model assisted with Question Cards while XI-IPA1 as the control group which received treatment using the lecture method assisted by Question Cards. The research data were obtained by means of test and observation. Based on the results of the study, the average value for the experimental group was 83.16 while for the control group an average value of 77 was obtained.Based on the analysis based on the learning outcomes, the experimental group's results were better than the control group as indicated by the tcount (3.59)> ttable (1.98). As for student activeness, it was found that the experimental group was better than the control group with the results of data analysis tcount (4.23)> ttable (1.98). solubility subject matter and solubility product, with the magnitude of the influence on student learning outcomes is 20.48% and the magnitude of the influence on student activeness is 27.04%.